Typology of farms and application of the assisted natural regeneration strategy in southwestern Burkina Faso - (:unkn) unknown (My University, 2022)
Faced with the multiple challenges of natural resource management, Assisted Natural Regeneration (ANR) is one of the strategies recommended especially in Africa for farmers. The present research therefore aims to study the characteristics of farms in relation to the strategy of application of Assisted Natural Regeneration (ANR) in agroecosystems in the southern Sudanian agro-climatic zone of Burkina Faso. The study took place on the outskirts of the Classified Forest and Partial Reserve of faun of Comoé Léraba located in the southwestern part of Burkina Faso. The methodological approach consisted of collecting socioeconomic data from 102 farms through a survey. The analysis of the results reveals that producers interested in ANR can be divided into three (03) distinct classes. It highlights the socioeconomic differences as well as the divergences in the conduct of the work of the ANR.
Keywords: African Research